Ultrastructural characterization of the olfactory organ in glass eels, Anguilla anguilla (Osteichthyes, Anguilliformes) - CARLA SOLA; GIULIANINI, PIERO GIULIO; FERRERO, ENRICO (Bolletino di zoologia, 1993)
The ultrastructure of the cell type complement of the olfactory epithelium in glass eels (Anguilla anguilla) is compared with the present knowledge of the olfactory organs in adult eels and in other fish species. In glass eel TEM sections, ciliary and microvillar receptor types are found. These sensory receptors occur on the central area of the lamellae and, in contrast to adults, are also located in lamellar infoldings and along the raphe. Peripherally in the lamellae located deep within the epithelium, more electrondense cell clusters consist of spindle‐shaped and oval cells giving off whorls of insunk cilia. These clusters are interpreted as differentiating units giving rise eventually to ciliated, supporting, and receptor cells.